De gröna näringarnas framtid : Är hjälpen som företagarcoacherna ger till landsbygdsföretagarna inom entreprenad, livsmedelsproduktion och turism tillräcklig och relevant? - Winneborn, Fredrik (2011)
The employment in the swedish country has diminished considerably since the beginning of the 20th century. The increased importation of food these days is forcing milk- and meat producers to find other business areas in order to make some money. The manufacturers of the countries in Norrbotten are good farmers but have, in general, limited knowledge about how to run a business. Lantbrukarnas Riksförbund started three years ago a project in order to help the farmers to become better business men. My study is focusing on whether or not this project is helping the farmers enough, if it is relevant and if the project lives up to its expectations. By research interviews I have produced this empirical material which have been analyzed with a tematic analyze in order to approach the problem: Is the help given from the manufacturers’ coaches by contract, production of food and tourism enough and relevant? The conclusion shows the sufficiency and relevance from the coaches and the manufacturers perspective and how they define this kind of help as a catchall term. As an educated journalist and an informant at Lantbrukarnas Riksförbund in Luleå, I am finally sharing some thoughts about my role as a researcher. Keywords: manufacture help, manufacturer coach, country manufacturers, communication, green nutriments, liberalism. Validerat; 20110621 (anonymous)